2017
DOI: 10.12669/pjms.335.13110
|View full text |Cite
|
Sign up to set email alerts
|

Association of single Nucleotide Missence Polymorphism Val109Aspof Omentin-1 gene and coronary artery disease in Pakistani population: Multicenter study

Abstract: Background & Objective:Coronary artery disease (CAD) is a most important cause of morbidity and mortality worldwide as well as in Pakistan. Recent studies have shown that the combination of obesity, insulin resistance and fluctuation in circulating adipocytokines levels is associated with the pathogenesis of coronary artery disease. Omentin-1 is recently found adipocytokine that is highly expressed in visceral adipose tissue. It has anti- inflammatory properties and is negatively correlated with ischemic heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
(15 reference statements)
5
11
0
Order By: Relevance
“…Our result also showed that the AT genotype of the rs2274907 is significantly more frequent in CAD patients than in controls ( P -value < 0.05, Table 3). This result is also in agreement with a recent study conducted in Pakistani population and demonstrated that AT genotype (Val/Asp (heterozygous mutant) of the rs2274907 is an association with the risk of CAD [18]. Our result also may be in accordance with previous findings suggesting that omentin has a cardioprotective effect [27] as a nitric oxide-mediated vasodilator [28], and that the plasma omentin is negatively associated with carotid intima-media thickness [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result also showed that the AT genotype of the rs2274907 is significantly more frequent in CAD patients than in controls ( P -value < 0.05, Table 3). This result is also in agreement with a recent study conducted in Pakistani population and demonstrated that AT genotype (Val/Asp (heterozygous mutant) of the rs2274907 is an association with the risk of CAD [18]. Our result also may be in accordance with previous findings suggesting that omentin has a cardioprotective effect [27] as a nitric oxide-mediated vasodilator [28], and that the plasma omentin is negatively associated with carotid intima-media thickness [23].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it was demonstrated that omentin enhances insulin sensitivity and that omentin protects against obesity and its comorbidities such as Type 2 diabetes (T2D) and CVDs [16]. Recently, Omentin-1 Val109Asp gene polymorphism has been shown to be associated with CAD in Pakistani and Iranian populations [17,18]. In the present study, we have examined the association of common polymorphisms [19] in the omentin gene, the rs2274907 A>T (Val109Asp) and rs2274908 G>A (His86His) (Figure 1) with CAD in the Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the relationship between omentin polymorphisms and the occurrence of CAD, for which MetS is a risk factor, gave inconclusive results. In the Pakistani population, it has been demonstrated that the heterozygous Val/Asp genotype of omentin-1 gene is more associated with the risk of developing CAD, while the homozygous genotype Asp/Asp reduces the risk of developing CAD [35]. A similar, although statistically insignificant tendency, was noted in the results of our research.…”
Section: Discussionsupporting
confidence: 88%
“…In Jha et al, 2019 [ 1 ], we report a potential association of the omentin SNP rs2274907 with CAD in a sample from a South Indian population. This result is consistent with previous studies conducted in Pakistani and Turkish populations [ 7 , 8 ], and to some extent in Iranian population [ 9 ]. Moreover, other studies reported an association of rs2274907 with type 2 diabetes [ 10 , 11 ], which is a risk factor for CAD.…”
supporting
confidence: 93%